(3GdeMGSHI aj GdefTBJ hGdeDSSGJ GdRQGYjI (B:s (3OQGSI eMGSHjI hGbJUGOjI (B/s - (3GdNWjH, NGdO QGZHs ((3YeGf(B: s (3OGQ GdHOGjI fGTQhf hehRYhf(B, s, 2010)
(3GdEbJUGO GdRQGYj(B- (3GdRQGYI hGbJUGOjGJgG(B- (3eTcdI GdZPGA aj GdYGde(B- (3CSGSjGJ JUeje GdfXGe GdeMGSHj(B- (3GSJNOGe GdMGSHGJ GdeGdjI hGdJcGdja GdRQGYjI aj GdefTBJ GdRQGYjI(B- (3GdYed GdEfSGfj(B- (3GdehGO GdChdjI(B- (3CfTWI GdefJLGJ GdRQGYjI(B- (3CfTWI GdeMGUjd GdMbdjI(B- (3JMOjO CQHGM HjY GdGQGVj aj GdTQcGJ GdRQGYjI(B- (3eTQhYGJ eGTjI GdGdHGf hGddMhe(B- (3GdMSGHGJ GdNJGejI aj GdefTBJ GdRQGYjIs
(3cTGa eUWdMGJ U(B239(3; GdeQGLY U(B269s
Keywords: (3GdEbJUGO GdRQGYjs; (3GdeMGSHIs; (3GdefTBJs